Museum, memory, and mental health: making sense of contestation over the interpretation of violence in the Contested Spaces exhibition at William Humphreys Art Gallery, Kimberley, South Africa - Niwenshuti, Theogene (African Studies, 2024)
The study sought to understand responses to Contested Spaces, an exhibition at the William Humphreys Art Gallery, Kimberley, South Africa. The long running exhibition (2016-2021) curated artworks dealing with colonisation, Apartheid and Post-Apartheid periods. It aimed to surface diverse views of the past by openly confronting contestations over colonial and Apartheid's violent histories. As artist and scholar in residence, my role was to document and facilitate responses to the exhibition. Initially, the ‘gaze'-focused and silent engagement with the exhibition did not generate much interaction. Through performance, hosting seminar conversations at which key artists engaged with their works, and inviting students, township residents, mental health practitioners and government officials to the gallery, I drew in new audiences. Immersive and experiential methods produced engagement in ways that the purely visual seemed not to generate. This enabled difficult conversations, including about generally taboo topics such as mental health and its relation to legacies of violence. Living with, and being exposed to memories of violence, can cause social and mental distress. These include feelings of being trapped, despairing and depressed. However, facilitated exposure can also enable a questioning of perspectives and an opening up of possibilities. Performance and conversation enabled participants to raise awareness of the impact of violence on social and mental wellbeing, and facilitated the formation of new subjectivities, enabling new ways of relating to each other. Through engagement with artistic expression, naming experience, reflecting on violation, and biometaphorisation, the dissertation argues that contestation is a complex embodied social phenomenon manifest in various forms. I have characterised these as Reactive, Strategic, Decorative, and Ritualistic. These forms overlap with three key qualities: Entrapment, Resistance and Flow. I propose Exit-Opening as a way of thinking beyond the state of what coparticipants described as feeling “trapped”, haunted by enduring violence. I argue that carefully facilitated conversations can generate potential exits from the ‘stuckness' of repetitive violence. The study shows how an anthropological and performative engagement with a context dominated by visual arts, museum and heritage studies can generate understanding and possibilities for social and mental health.